Sales and Business Models in the Logistics Industry Ensuring Growth with Innovative Strategies - Nowroth, Alexander (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
The logistics industry is changing rapidly. In this fiercely competitive sector, predominantly static sales organizations are working hard at keeping their companies on track for success. However, the existence of these companies has never been more at risk than it is today, as most not only have outdated IT systems, but also rely on suboptimal commercial structures. Most companies have fallen far short of their earnings potential, especially during the high freight rate increases of recent years, and in terms of sales volume, they are no longer growing at a sufficient pace or are even risking their continued existence. This book studies how logistics service providers can develop powerful strategies for sustainable growth and position themselves for future success. The author outlines these new rules using examples and step by step guides to take readers through the emerging trends and to outline strategies required to meet the changing demands of the future. The book also makes clear how logistics companies can establish a lasting high-performance culture among their sales teams and how to succeed in winning over sales staff and retaining them in the long term. The author Alexander Nowroth is Managing Partner of LEBENSWERK CONSULTING GROUP based in Düsseldorf, Germany. His consulting clients range from well-known corporations to large family-owned enterprises, all benefiting from his international experience in the shipping and logistics industry.
Status quo: market and competitive situation -- The players in the market: shipping companies, airlines, logistics service providers, start-ups -- Sales models, analog and digital sales strategies in the logistics industry -- Customer behavior and customer needs today and in the future -- Sales performance of employees and teams -- Increasing the ROI of sales capacity.-Cross-selling as a sales turbo.
Keywords: Sales management; Business logistics; Marketing; Sales and Distribution; Logistics; Marketing